O ensino de filosofia africana no contexto da lei 10.639/03: uma proposta de ensino para a Unidade Integrada Sarney Filho no município da Raposa/Maranhão - BARBOSA, Rosinélia Machado (2024)
The research deals with TEACHING AFRICAN PHILOSOPHY IN THE CONTEXT OF LAW 10.639/03: a teaching proposal for the Sarney Filho Integrated Unit in the Municipality of Raposa/Maranhão. The Study's general objective is to investigate the philosophical contents developed at the Sarney Filho Integrated Unit, with a view to building a Booklet of Teaching Guidelines, together with the Philosophy teacher on the teaching of African philosophical themes, in order to add to the curricular proposal of philosophy of Elementary Education, final years, in the municipality of Raposa-MA. The main bibliographical sources used in this study: Asante (2000, 2009); Appiah (2010); Hountondji (1006); Noguera (2014); Dantas (2014); Nascimento and Rocha (2016); Nascimento (2002); Law No. 10,639/03 (BRAZIL, 2003); National curricular guidelines for the education of ethnic-racial relations and for the teaching of Afro-Brazilian and African history and culture. (BRAZIL, 2008); Cliver (2020); Castro (2020). The work is organized into the following sections: in the first, we discuss the introduction to the theoretical and methodological configuration of the research; in the second section, it presents some questions about the controversial discussion about the place, territory in which philosophical knowledge emerged, Greece or Africa (Specifically on the soil of Ancient Egypt), without the intention of invalidating any of the theories, only allowing readers to broaden their epistemic horizons. In the third section, we will present African Philosophy: the black population as a subject of its history. This section is subdivided into three subsections: Afroperspectivism; Afrocentrism; Ethnophilosophy. In the fourth section, we discuss the empirical research, which was divided into three subsections, the characterization of the Sarney Filho Integrated Unit; the research methodology: Analysis and Interpretation of Research data and the educational product; In the fifth section, we will present final considerations. The research procedure method adopted was the instrumental case study. The research participants were the school manager, the pedagogical supervisor and the philosophy teacher from the 9 th A and B classes. Due to the pandemic period caused by the Covid/19 virus, our data collection instruments were interviews, carried out through interviewees’ social networks. The interpretation of empirical research data was in the form of tables. The empirical research was developed in two moments: interviews through the participants' social networks and composition of the final product. The research concluded that the inclusion of African philosophical themes in the context of Law 10.639/03 in the curriculum enabled the Sarney Filho school community to demystify the existence of African philosophical productions, allowing the teacher to develop themes relating to ethnic-racial relations.